2016
DOI: 10.1002/lt.24453
|View full text |Cite
|
Sign up to set email alerts
|

Protective role of normothermic machine perfusion during reduced‐size liver transplantation in pigs

Abstract: The purpose of this study is to explore whether normothermic machine perfusion (NMP) preservation is superior to cold preservation during reduced-size liver transplantation (RSLT) in pigs. Twenty-four healthy Ba-Ma mini pigs were used (aged >13 months; weight 25-35 kg; regardless of sex). The animals were randomized into 2 groups. In group A (NMP), donor livers were harvested without warm ischemia time and heartbeats and then were connected to the NMP system to reduce the livers' size under the normothermic co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…An isolated organ model with vascular perfusion and the possibility of keeping an entire human liver viable for a few days should allow us to evaluate the entire decoding process after hydrofection, from delivery to protein translation and export into the circulating medium. At present, different devices for maintaining liver circulation ex vivo are being used in the field of liver transplantation, such as Organox ® and other experimental systems have been proposed [ 159 ]. Our group has already designed and constructed a preliminary system offering the possibility of liver maintenance for up to two days for preclinical studies.…”
Section: Hydrodynamic Genes Transfer To Human Organ Ex Vivomentioning
confidence: 99%
“…An isolated organ model with vascular perfusion and the possibility of keeping an entire human liver viable for a few days should allow us to evaluate the entire decoding process after hydrofection, from delivery to protein translation and export into the circulating medium. At present, different devices for maintaining liver circulation ex vivo are being used in the field of liver transplantation, such as Organox ® and other experimental systems have been proposed [ 159 ]. Our group has already designed and constructed a preliminary system offering the possibility of liver maintenance for up to two days for preclinical studies.…”
Section: Hydrodynamic Genes Transfer To Human Organ Ex Vivomentioning
confidence: 99%
“…An induction of inflammatory pathways was shown in different organs. Zhang et al compared NMP with SCS in a reduced-size LT pig model and confirmed the presence of serum markers of oxidative tissue damage (malondialdehyde) and inflammatory cytokines (TNF-α, IL-1, IL-6) postoperatively [113]. In order to provide the complete picture, it would be of interest not only to measure the plasma levels of inflammatory markers, which were significantly lower in the NMP group, but also to quantify the same markers in the perfusates obtained from the device [113].…”
Section: Normothermic Machine Perfusion Of the Liver (Nmp)mentioning
confidence: 94%
“…Zhang et al compared NMP with SCS in a reduced-size LT pig model and confirmed the presence of serum markers of oxidative tissue damage (malondialdehyde) and inflammatory cytokines (TNF-α, IL-1, IL-6) postoperatively [113]. In order to provide the complete picture, it would be of interest not only to measure the plasma levels of inflammatory markers, which were significantly lower in the NMP group, but also to quantify the same markers in the perfusates obtained from the device [113]. In addition, NMP promoted a significant reduction of molecules associated with apoptosis (cytochrome C, caspase 3) and cytokines and chemokines synthesis and secretion (NF-κB; p65) [113].…”
Section: Normothermic Machine Perfusion Of the Liver (Nmp)mentioning
confidence: 94%
“…NMP has been used in a pig model of liver transplantation, simulating in-vivo liver resection and improving preservation. This strategy resulted in better post-transplantation outcomes when compared with the outcomes of livers that underwent reduction in SCS [56]. There have been reports of hepatocyte replication and biliary epithelial cell regeneration being detected during NMP [57, 58], and one can imagine also growing livers during NMP to either jumpstart the growth of a small liver prior to transplantation or a longer-term perfusion actually increasing the size of a small segment prior to transplantation.…”
Section: Machine Perfusion: a Platform For Organ Treatmentmentioning
confidence: 99%